Eksistensi Justice Collaborator dalam Tindak Pidana Pembunuhan Berencana Berdasarkan Hukum Pidana di Indonesia - James V. L. Pontoh; Yulia Vera Momuat; Geraldy J. G. Worang (LPPM Universitas Ekasakti Padang, 2023)
Justice collaborators are seen as having a strategic role in bringing to light criminal incidents, but in their development justice collaborators still bring controversy. Justice collaborators themselves can be understood as perpetrator witnesses who work together to reveal the true facts in certain criminal acts. The aim of this research was to analyze the existence of justice collaborators in the Indonesian judiciary and to determine the form of legal certainty for justice collaborators in the crime of malice aforethought. This research was conducted using the normative juridical methodology, where the author used sources in the form of the 1945 Constitution of the Republic of Indonesia, laws, scientific journals, books, the Big Indonesian Dictionary, and other research results. The results of the research showed that the existence of justice collaborators in Indonesia must be proven judicially, and it is necessary to realize that the role of justice collaborators in a particular criminal case is very strategic, so that legal certainty for justice collaborators must be guaranteed by the state, considering their strategic role. so that the safety of the justice collaborator after testifying in court becomes vulnerable to terror from parties who are not in line with their role. Suggestions for the development of justice collaborators in Indonesia are that a view should be developed that the role of justice collaborators is very strategic in uncovering a criminal case and the regulation of justice collaborators should be included in a law that specifically regulates justice collaborators.